Analisis Pengembangan Usaha Mikro Kecil Dan Menengah (Umkm) di Kelurahan Klampok Kota Blitar - Gideon Setyo Budiwitjaksono; Rima Anggun Aprilya; Sintha Dayu Aringgani; Devi Istyalita; Wakhidatul Ummah; Moch. Rizky Ramadhan (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
Small and Medium Enterprises (MSMEs) in Klampok City, in running their business, handle problems related to almost all assets, both raw materials, finance, advertising, work, innovation and also the views of the management. The data checking procedure used is a separate inspection method because the information obtained is subjective, namely by distributing opinion polls using a real scale. The factor that creates this problem is largely due to the low level of training and education in business that business entertainment executives have. Most financial experts feel that they have sufficient business knowledge and skills, so they are not too eager to add their business information, especially if they need to pay cash to get this information. The problem of capital is a well-known one that almost all types of businesses face. The problems of MSMEs in Klampok District inspired researchers to develop solutions starting from NIB, product branding with improved packaging and logos or brands, business analysis with business plans, online bookkeeping system assistance, and product digitization with a more modern online marketing system. way to increase sales.